2018
DOI: 10.1055/s-0038-1656511
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound for the Hepatologist: A Comprehensive Review

Abstract: In the last few years, the diagnostic and therapeutic utilization of endoscopic ultrasound (EUS) for a variety of liver conditions has exponentially grown. We performed a thorough search for all available studies on the performance of diagnostic and therapeutic EUS in the field of hepatology. This article reviews the indication of EUS in the evaluation and treatment of portal hypertension, portal vein pressure measurement, focal liver lesions, and parenchymal liver diseases, and presents all the clinical evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 109 publications
(117 reference statements)
0
11
0
Order By: Relevance
“…is trial also showed that persisting esophageal collateral vessels after sclerotherapy was a statistically significant risk factor for recurrence (p � 0.003) [33]. Decompression of portal system by creating a low-resistance channel between portal vein and inferior vena cava is usually achieved by Transjugular Intrahepatic Portosystemic Shunt (TIPSS) procedure [26].…”
Section: E Role Of Endoscopic Ultrasound In Portal Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations
“…is trial also showed that persisting esophageal collateral vessels after sclerotherapy was a statistically significant risk factor for recurrence (p � 0.003) [33]. Decompression of portal system by creating a low-resistance channel between portal vein and inferior vena cava is usually achieved by Transjugular Intrahepatic Portosystemic Shunt (TIPSS) procedure [26].…”
Section: E Role Of Endoscopic Ultrasound In Portal Hypertensionmentioning
confidence: 99%
“…These advantages may be contributed by real-time ultrasound guidance, rapid recovery time, the possibility of producing several needle actuations within the liver with only a single puncture through the liver capsule [ 24 ]. Moreover, it has been estimated that the potential sampling errors of single-blind percutaneous liver biopsy for detection of cirrhosis may occur in up to 30% cases [ 26 ].…”
Section: The Diagnostic Role Of Endoscopic Ultrasoundmentioning
confidence: 99%
See 1 more Smart Citation
“…The current standard for evaluation of PH is an indirect measurement of HVPG via right jugular vein access, where the free hepatic venous pressure is recorded and subtracted from the wedged hepatic venous pressure to determine the HVPG. Despite the overall safety profile, the method is highly invasive and requires technical expertise found at specialized medical centers and may not always accurately reproduce true portal venous pressures, especially in patients with pre-and post-hepatic etiologies of PH [4,56]. Direct percutaneous portal vein catheterization is usually avoided because of the high risk for complications [57].…”
Section: Eus-guided Portal Hypertension Measurementmentioning
confidence: 99%
“…Endoscopic ultrasound (EUS) is an unavoidable method for the evaluation of the pancreatobiliary and upper gastrointestinal tract with an expanding role in the field of hepatology. The limitations of conventional diagnostic tools and percutaneous interventions for liver disease, mostly done with transabdominal ultrasound (US) or computed tomography (CT) guidance, have made EUS an attractive alternative, predominantly due to the enhanced imaging quality and safety profile along with the biopsy acquisition ability regardless of body habitus [3,4].…”
Section: Introductionmentioning
confidence: 99%